World-wide seasonal variation of 7Be related to large-scale atmospheric circulation dynamics. (November 2017) - Terzi, Lucrezia; Kalinowski, Martin
Highlights: Analysis of 7 Be activity values measured from 63 IMS stations worldwide from 2001 to 2015. Observed 7 Be global seasonal variation as an expression of atmospheric cell migration, ITCZ and HFCZ. Reconstruction of a global 7 Be concentration map over time. Correlation between 7 Be global patterns with tropopause height, Walker circulation, SSW, SEP and QBO. Onsets of 7 Be activity concentrations as early warning indicator for emerging El Niños and Indian monsoons.